2023
DOI: 10.1039/d2cc05314d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a meltable purinate metal–organic framework and its glass analogue

Abstract: The chemistries that can be incorporated within melt-quenched zeolitic imidazolate framework (ZIF) glasses are currently limited. Here we describe the preparation of a previously unknown purine-containing ZIF which we name...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…For example, both ZIF-4 and another isostructural mixed-linker compound, ZIF-62, Zn­(Im) 1.75 (bIM) 0.25 , have the cag topology. ,, It was found that the melting point of ZIF-62 was primarily affected by the presence of bulkier bIm linkers, and therefore adjusting the Im/bIm ratio in ZIF-62 can render the porous and tunable glassy ZIFs for gas separation . Subsequent discoveries, such as the ZIF-UC family, further highlighted the possibility of using a mixed-linker structure to produce cag topology ZIFs. This is achieved by replacing the bIm linker in ZIF-62 with differently functionalized bIm, leading to a variety of new ZIFs with altered thermal behaviors.…”
Section: Structure–property Relationship Of Zifsmentioning
confidence: 99%
“…For example, both ZIF-4 and another isostructural mixed-linker compound, ZIF-62, Zn­(Im) 1.75 (bIM) 0.25 , have the cag topology. ,, It was found that the melting point of ZIF-62 was primarily affected by the presence of bulkier bIm linkers, and therefore adjusting the Im/bIm ratio in ZIF-62 can render the porous and tunable glassy ZIFs for gas separation . Subsequent discoveries, such as the ZIF-UC family, further highlighted the possibility of using a mixed-linker structure to produce cag topology ZIFs. This is achieved by replacing the bIm linker in ZIF-62 with differently functionalized bIm, leading to a variety of new ZIFs with altered thermal behaviors.…”
Section: Structure–property Relationship Of Zifsmentioning
confidence: 99%
“…In a different example, the substitution of benzylimidazolate with purinate (pur − ) in the ZIF-62 structure led to increased CO 2 uptake capacity for both the resulting crystalline and glass ZIF-UC-7, Zn(Im) 1.75 (pur) 0.25 . 126…”
Section: Non-reversible High Temperature Phase Transitionsmentioning
confidence: 99%
“…In a different example, the substitution of benzylimidazolate with purinate (pur À ) in the ZIF-62 structure led to increased CO 2 uptake capacity for both the resulting crystalline and glass ZIF-UC-7, Zn(Im) 1.75 (pur) 0.25 . 126 Recently, imidazole was substituted in ZIF-4 by an imidazole containing cyano groups, forming ZIF-4-CNx materials, with the following compositions: [Zn(Im) 2Àx (CNIm) x ] CNIm À = 4cyanoimidazolate, (0.04 r x r 0.39) and [Zn(Im) 2Àx (dCNIm) x ], dCNIm À = 4,5-dicyanoimidazolate, (0.10 r x r 0.28). 127 This family of materials melts and forms melt-quenched glasses with a range of T g s between 527 K and 249 K that can be easily varied controlling the Im/CNIm ratio.…”
Section: Melting and Vitrification Behaviourmentioning
confidence: 99%
“…5 and 6). 22 Scanning electron microscopy (SEM) analysis showed that after vitri cation through cooling to room temperature, shards of G-Mg-adp display a smooth surface (Fig. 1e).…”
Section: Full Textmentioning
confidence: 99%